Following butter flavour deterioration with an acoustic wave sensor - Gaspar, Cláudia R. B. S. (2019)
Off-flavours develop naturally in butter and the process is accelerated by heat. An acoustic wave sensor was used to detect the aroma compounds evolved from heated butter and the results have shown that registered marked changes were coincident to odour changes detected by sensory analysis. The flavour compounds have also been analysed by GC/MS for identification. The response of the sensor was fully characterized in terms of the sensitivity to each of the identified compounds, and sensitivities of the system SPME/sensor were compared with the sensitivities of the system SPME/GC/MS. It was found that the sensor analytical system was more sensitive to methylketones than to fatty acids. The SPME/GC/MS system also showed the highest sensitivity to 2-heptanone, followed by 2-nonanone, but third place was occupied by undecanone and butanoic acid, to which the sensor showed moderate sensitivity. 2-heptanone was found to be an appropriate model compound to follow odour changes till the 500 h, and the lower sensitivity of the sensor to butanoic acid showed to be a positive characteristic, as saturation was prevented, and other more subtle changes in the flavour could be perceived.